APLIKASI GAME “SEMAPHORE” BERBASIS ANDROID - Andi Muh. Syahrul; Mina Ismu Rahayu (LPPM STMIK BANDUNG, 2019)
Android-Based Semaphore Game application is one of semaphore cue learning or training media that utilizing technology. Gameplay in the form of quizzes can help players to train their memorization or memory. Not only that, the variation of the questions and time to answer varying in each level makes this application a challenging game. Semaphore learning, especially in scouting, is usually done when scouting activities take place only. Beyond these activities, semaphore learning is limited due to the lack of interest and sometimes time and place that is not appropriate to learn semaphore. Prototype method with system design using Unified Modeling Language (UML) is used to develop the software. Game engine Unity is used to develop the application. This application that running on a mobile device not only makes learning semaphore practically carried everywhere but also allows learning or practicing semaphore anytime and anywhere. It also becomes a new method to learn semaphore. Moreover, this application is packed in the form of a fun game that can attract interest.